Uji Mutu Benih Beberapa Varietas Padi (Oryza sativa) pada Berbagai Periode Umur Simpan - Asmary Muis; Firmansyah Firmansyah (Gunung Djati Conference Series, 2021)
Rice seed quality can be decreased during in storage. High quality seeds has high viability and vigor. The experiment was aimed to know the effect of seed storage duration on rice seed quality and to determine the variety that has a longer shelf life. The experiment was conducted in the Laboratory of Seed, Tungro Disease Research Center Lanrang, Sidrap, South Sulawesi, from July 2019 until January 2020. The experiment was arranged in the completely randomized design (CRD) with two factors. Each treatment combination consisted of 4 replications. The first factors was storage duration that consisted of four levels: 3 months, 5 months, 7 months, and 9 months. The second factors were variety that consisted of five varieties: Tukad Balian, Tukad Petanu, Situ Patenggang, Cigeulis, and Towuti. Variables observed were seed moisture content and maximum growth potential. The results showed that storage duration influenced the seed moisture content and maximum growth potential. Increasing storage periods of rice seed from 5, 7, and 9 months after harvesting decreased the seed moisture content of Tukad Balian and Situ Patenggang but it increased the seed moisture content of Tukad Petanu. Increasing storage periods of rice also decreased maximum growth potential of Tukad Balian, Situ Patenggang, and Tukad Petanu. Meanwhile, Cigeulis and Towuti can maintain their seed moisture content and maximum growth potential up to 9 months.